PELATIHAN PENGEMBANGAN USAHA DENGAN MENERAPKAN PRINSIP-PRINSIP SYARIAH PADA BADAN USAHA MILIK DESA (BUMDES) BANJAREJO KECAMATAN PANEKAN KABUPATEN MAGETAN - Christanti, Yana Dwi; Anggraeny, Shinta Noor; Amir , Vaisal (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2024)
Rural areas hold enormous economic potential, and to optimize this potential, Village-Owned Enterprises (BUMDes) have a very crucial role. The intention of this service initiative is to enhance the skills and capabilities of BUMDes employees by providing training and advisory support. The material presented includes important aspects related to Sharia BUMDes Finance, Sharia Economic Principles, Sharia Financial Products, and Sharia Agreements. By understanding and implementing these principles, it is expected that BUMDes Banjarejo can run its business better, uphold the values of justice and blessings, and make a significant contribution to the welfare of the village community.